2006
DOI: 10.1111/j.1365-2265.2006.02543.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HRT on liver enzyme levels in women with type 2 diabetes: a randomized placebo‐controlled trial

Abstract: HRT containing low-dose oestradiol and norethisterone reduces serum concentrations of liver function enzymes, potentially due to a lowering of liver fat accumulation. Better understanding of mechanisms by which this HRT improves liver function tests could help the design of new therapies to treat individuals with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 25 publications
11
80
1
1
Order By: Relevance
“…These results may suggest a possible relation of HRT in a less liver injury, and they are in agreement with a study performed in Scotland, which suggested that HRT improved the results of liver-enzyme levels in women with type 2 diabetes (16) . However, in both studies was not performed liver biopsy, that remains the gold standard for diagnosis and staging of hepatic fibrosis (24) .…”
Section: Discussionsupporting
confidence: 81%
“…These results may suggest a possible relation of HRT in a less liver injury, and they are in agreement with a study performed in Scotland, which suggested that HRT improved the results of liver-enzyme levels in women with type 2 diabetes (16) . However, in both studies was not performed liver biopsy, that remains the gold standard for diagnosis and staging of hepatic fibrosis (24) .…”
Section: Discussionsupporting
confidence: 81%
“…We saw that a short 2 month course without HRT lead to elevation of liver enzymes, readily suppressible by standard HRT, as also documented previously (3)(4)(5). Recently, the same response to HRT, albeit less pronounced, has also been found among postmenopausal women (27). Thus, lack of estrogens in some way seems to affect the liver.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, in an OVX SpragueDawley rat model, 17b-estradiol treatment decreased fatty acid synthesis in a hepatic zone 3-specific manner through increasing the phosphorylation of acetyl coenzyme-A carboxylase via an estrogen receptor-a-mediated pathway (Zhang et al 2013). Menopausal women have been shown to exhibit hepatic steatosis which is ameliorated by estrogen replacement therapy, although the results are inconsistent (Florentino et al 2013;McKenzie et al 2006). Thus, the activation of estrogen receptors in the liver may prevent hepatic steatosis by increasing b-oxidation of fatty acids and decreasing lipogenesis.…”
Section: Discussionmentioning
confidence: 99%